sensor

The sensor with a metal nanoparticle layer on the inner surface of a well plate addresses the inefficiencies of traditional culturing methods by enabling rapid, high-sensitivity detection of microorganisms through surface plasmon coupling.

JP7664639B2Active Publication Date: 2025-04-18PUBLIC UNIVERSITY CORPORATION OSAKA CITY UNIVERSITY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022517118
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-04-22
Filing Date
2021-04-13
Publication Date
2025-04-18
Estimated Expiration
2041-04-13

AI Technical Summary

Technical Problem

Current methods for detecting microorganisms, such as those used in microbial contamination detection, require culturing processes that are time-consuming and inefficient for detecting trace amounts of bacteria.

Method used

A sensor with a metal layer formed by a plurality of metal nanoparticles on the inner wall surface of a well plate, which enables high-sensitivity detection through surface plasmon coupling, allowing for rapid detection of microorganisms without the need for culturing.

Benefits of technology

The sensor enables quick and easy detection of fine objects, reduces or eliminates the need for culturing, and enhances optical properties for improved sensitivity, making it suitable for rapid microbial detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664639000003
    Figure 0007664639000003
  • Figure 0007664639000004
    Figure 0007664639000004
  • Figure 0007664639000005
    Figure 0007664639000005
Patent Text Reader

Abstract

The present invention provides a sensor capable of quickly and easily detecting a minute detection target. Provided is a sensor 1 which is for detecting a detection target and which comprises a well plate 10 and a metal layer that is formed from a plurality of metal nanoparticles 21a on the inner wall surface of a well 20 in the well plate 10. The sensor 1 is preferably for collectively detecting a plurality of items pertaining to the detection target, or for collectively detecting the detection target in a plurality of samples. The metal layer is preferably a metal nanoparticle layer 21 formed from a plurality of aligned metal nanoparticles 21a or a metal plating layer 22 formed from metal nanoparticles 21a.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sensor for detecting an object to be detected. [Background technology]

[0002] In recent years, interest in microbial detection has been growing in the medical industry, food industry, agriculture, livestock farming, aquaculture, water treatment facilities, and the like. Contaminating microorganisms present in foods, medicines, agricultural products, and seafood can have a significant impact on human health, even though they are present in small amounts. In addition, microbial contamination in hospitals and nursing homes for the elderly has become a social problem. Furthermore, as seen in the increasing distribution and demand for various antibacterial products, interest in hygiene management in ordinary households is also increasing. For example, in food processing factories, bacterial tests are conducted on sampled foods to be shipped and on the environment within the factory. However, in the case of measurement using the culture method, it takes about 24 to 48 hours to obtain results, which is a factor in increasing the storage costs until shipment, so a rapid detection method is required. In the agricultural field, for example, an increase in the number of bacteria in the culture solution for hydroponic cultivation increases the risk of illness. A rapid detection method is effective because measures such as sterilization can be taken quickly by quickly grasping the number of bacteria.

[0003] In light of this situation, the need for technology that can easily detect microbial contamination has been rapidly increasing in recent years. In addition, in the medical field, it is necessary to quickly identify the pathogen that causes an infectious disease, so there is a demand for technology that can detect pathogens quickly and with high sensitivity. For example, ELISA and Western blotting are known as methods for detecting and identifying microorganisms. These are methods in which, for example, an antibody (primary antibody) is reacted with a protein specific to a microorganism through an antigen-antibody reaction, and then a labeled secondary antibody is reacted with the antigen, and detection is performed by monitoring the chemiluminescence of the secondary antibody or the hydrolysis reaction of ATP.

[0004] Plate readers are known as microbial detection devices. Plate readers can simultaneously detect changes in absorbance and fluorescence caused by reactions in the wells of a microplate. In microanalysis and screening, it is important for plate readers to measure optical signals caused by reactions in the wells with high sensitivity.

[0005] A plastic microplate is known to have a structure in which a polymer for binding antigens, antibodies, etc. is arranged on the inner wall of the wells to make it applicable to the ELISA method (see, for example, Non-Patent Document 1). The above-mentioned microplate enables selective detection of microorganisms. In the MTT assay and ELISA method using a microplate and a plate reader, the detection limit is determined by the absorption coefficient and fluorescence coefficient of the dye. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Paul Machillot,et al.,Advanced Materials,2008,30,1801097 Summary of the Invention [Problem to be solved by the invention]

[0007] In the case of detection using microplates, a process of culturing and growing microorganisms is necessary to obtain sufficient sensitivity in measurements targeting microorganisms. Therefore, when it is necessary to detect minute amounts of bacteria, such as in sterility tests, there is a problem in that it takes a long time to culture the bacteria.

[0008] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a sensor capable of quickly and easily detecting a minute object to be detected. [Means for solving the problem]

[0009] As a result of intensive research into achieving the above object, the present inventors have found that a sensor having a metal layer formed of a plurality of metal nanoparticles on the inner wall surface of a well in a well plate can detect an object to be detected with high sensitivity by surface plasmon coupling or the like using the metal nanoparticles, thereby shortening or eliminating the culture process of microorganisms, etc., and enabling rapid and simple detection of minute objects to be detected. The present invention has been completed based on these findings.

[0010] That is, the present invention provides a sensor for detecting an analyte, comprising a well plate and a metal layer having a thickness of 1 to 100 nm and formed on the inner wall surface of a well in the well plate and composed of a plurality of metal nanoparticles.

[0011] The sensor is preferably one for simultaneously detecting multiple items related to the analyte, or for simultaneously detecting the analyte in a plurality of samples.

[0012] The metal layer is preferably a metal nanoparticle layer formed by arranging the plurality of metal nanoparticles or a metal plating layer formed from the metal nanoparticles.

[0013] When the metal layer is a metal plating layer, it is preferable that the metal plating layer is uniformly formed on the inner wall surface of the well.

[0014] When the metal layer is a metal nanoparticle layer, the distance between the metal nanoparticles in the metal nanoparticle layer is preferably 2 to 200 nm.

[0015] The metal nanoparticles preferably contain one or more metal elements selected from the group consisting of gold, silver, platinum, palladium, copper, nickel, iron, titanium, zinc, aluminum, tungsten, zirconia, and tin, and are composed of a single metal or a metal compound.

[0016] The average particle size of the metal nanoparticles is preferably 1 to 100 nm.

[0017] The metal layer may be exposed in the well. Also, a specific binding substance may be disposed on the metal layer in the well, in which case the metal layer may exert a surface plasmon resonance or surface plasmon coupling effect.

[0018] The well plate is preferably a microwell plate.

[0019] The amount of the metal nanoparticles in one well is 1 μg / cm 2 More preferably, it is equal to or greater than this.

[0020] The surface resistance value of the metal layer in each well is preferably 0.3 MΩ / mm or more.

[0021] The well plate is preferably a 6-well, 24-well, 96-well, or 384-well microwell plate. Effect of the Invention

[0022] The sensor of the present invention can detect minute objects quickly and easily, and can be easily recovered and reused. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a schematic diagram showing an embodiment of a sensor of the present invention. [Diagram 2] 2A and 2B are cross-sectional views taken along the line II-II' of the sensor shown in FIG. 1, in which (a) shows a metal layer in which the metal nanoparticles are layered, and (b) shows a metal layer in which the metal layer is a metal plating layer. [Diagram 3] 1 is a schematic diagram showing an embodiment of a sensor in which a resin layer having a detection site capable of detecting an object to be detected is formed on a metal layer. [Figure 4]4 is a schematic diagram showing a state in which an object to be detected has been taken into a detection site of the sensor shown in FIG. 3. [Diagram 5] FIG. 5 is a schematic diagram showing a state in which a resin layer has undergone phase transition in the sensor shown in FIG. 4. [Figure 6] The fluorescence spectra obtained when (a) a gold nanoparticle dispersion and (b) a silver nanoparticle dispersion were dropped into a 1 μM aqueous solution of fluorescein are shown. [Figure 7] 1 shows a top view photograph of a sensor prepared in Example 1, in which a metal nanoparticle layer is formed on the inner wall surface of a well. [Figure 8] 1 shows an SEM image of a silver nanoparticle layer formed on the inner wall surface of a well in a sensor in which silver nanoparticles are immobilized on the inner wall surface of a well, as prepared in Example 1. [Figure 9] 1 shows a top view photograph of the sensor in which silver nanoparticles are immobilized on the inner wall surface of the well, prepared in Example 2. [Figure 10] FIG. 13 is a graph showing, in Example 2, (a) the absorption spectrum of a silver nanoparticle dispersion and the UV-vis absorption spectrum of a well after silver nanoparticles are fixed using the dispersion, and (b) the relationship between the concentration of the dispersion and the amount of silver nanoparticles fixed to the inner wall of the well. [Figure 11] (a) Absorption spectrum of the bottom surface of the well where silver nanoparticles are immobilized in the sensor prepared in Example 2, (b) absorption spectrum of the bottom surface of the well where gold nanoparticles are immobilized in the sensor prepared in Example 1, and (c) a graph plotting the absorption peak at 410 nm against the amount of silver nanoparticles immobilized. [Figure 12] 13A is a graph showing the fluorescence intensity of wells to which various metal nanoparticles were immobilized in Example 4, and FIG. 13B is a graph showing the relationship between the amount of immobilized silver nanoparticles (30 nm) and the fluorescence intensity. [Figure 13] FIG. 13 is a graph showing (a) the change in fluorescence intensity of a silver nanoparticle-immobilized well versus the amount of avidin in Example 5, (b) an enlarged view of the fluorescence intensity of 0 to 2000 in (a), and (c) the change in fluorescence intensity at avidin amounts of 0 to 25 pmol. [Figure 14]1 shows a top view photograph of a sensor on which a gold plating layer and a silver plating layer are formed in Example 6. [Figure 15] FIG. 13 shows (a) a graph showing the change in fluorescence intensity over time with respect to the number of bacteria in Example 7, and (b) an enlarged view of (a) where the number of bacteria is in the range of 0 to 2000. [Figure 16] 1 shows micrographs of the counting of the number of bacterial cells adsorbed to (a) a silver nanoparticle-immobilized well and (b) an unmodified well in Example 7. [Figure 17] 1 is a graph showing the fluorescence intensity in the fluorescence spectrum measurements of (a) S. enterica, (b) E. coli O26, and (c) E. coli O157 performed in Example 8. [Figure 18] 1 is a graph showing the change in fluorescence intensity for each number of mixed E. coli O26 cells, as performed in Example 8. [Figure 19] 1 is a graph showing (a) fluorescence intensity versus virus concentration (μg / mL) and (b) fluorescence intensity versus number of virus particles (particles) in the fluorescence intensity measurements performed in Example 10. [Figure 20] 1 is a graph showing (a) fluorescence intensity versus virus concentration (μg / mL) and (b) fluorescence intensity versus number of virus particles (particles) in the fluorescence intensity measurements performed in Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] [sensor] The sensor of the present invention is a sensor for detecting an object to be detected. The sensor of the present invention includes a well plate and a metal layer formed on the inner wall surface of the well in the well plate. The metal layer is formed of a plurality of metal nanoparticles and has a film thickness of 1 to 100 nm. In the sensor of the present invention, by providing the metal layer having a film thickness of 1 to 100 nm on the inner wall surface of the well, even if the amount or concentration of the object to be detected is small, the object to be detected can be detected with high sensitivity by enhancing optical properties such as reflection intensity and fluorescence intensity due to surface plasmon resonance by the metal nanoparticles and the coupling effect of the surface plasmon. Therefore, the culture process of microorganisms and the like can be shortened or omitted, and minute objects to be detected can be detected quickly and simply. In addition, since the metal layer is fixed to the inner wall surface of the well, it can be easily collected and reused after use, and can be used repeatedly.

[0025] The sensor of the present invention is preferably for detecting multiple items related to the analyte at once, or for detecting the analyte in multiple samples at once. For example, by preparing metal layers each having binding affinity with different analytes in multiple wells, the same sample can be put into the multiple wells to detect multiple items related to the analyte in the sample at once. In addition, by preparing metal layers each having binding affinity with any analyte in multiple wells, the same analyte in multiple samples can be detected at once, and the sensitivity of the analyte can be relatively evaluated.

[0026] Examples of the metal layer formed by the plurality of metal nanoparticles include a metal nanoparticle layer formed by arranging the plurality of metal nanoparticles, and a metal plating layer formed by the metal nanoparticles. The metal nanoparticle layer is a layer formed by a plurality of metal nanoparticles while the plurality of metal nanoparticles maintain the shape of nanoparticles. The metal plating layer formed by the metal nanoparticles can be formed, for example, by growing the metal nanoparticles in the metal nanoparticle layer. According to this method, the metal nanoparticles are arranged up to the corners of the well, and then the metal nanoparticles are grown to form the metal plating layer, so that a more uniform layer can be formed up to the corners inside the well than a method in which a separately prepared metal film is attached to the inner wall of the well. Therefore, the metal plating layer is formed uniformly on the inner wall surface of the well.

[0027] The metal layer has a thickness of 1 to 100 nm. When the thickness is within this range, optical properties such as reflection intensity and fluorescence intensity can be enhanced by surface plasmon resonance due to metal nanoparticles and a coupling effect of the surface plasmon, enabling detection of an object with high sensitivity.

[0028] One embodiment of the sensor of the present invention is shown in Fig. 1 and Fig. 2. Fig. 2 is a cross-sectional view of the II-II' section of the sensor 1 shown in Fig. 1, Fig. 2(a) shows a view in which the metal layer is a metal nanoparticle layer, and Fig. 2(b) shows a view in which the metal layer is a metal plating layer. The sensor 1 shown in Fig. 1 and Fig. 2 includes a well plate 10 having a plurality of wells (bottomed holes) 20, and a metal nanoparticle layer 21 formed on the entire wall surface including the bottom and side walls in the plurality of wells 20. In Fig. 2(a), the metal nanoparticle layer 21 is formed by arranging and fixing a plurality of metal nanoparticles 21a on the inner wall surface of the well 20 while maintaining the shape of nanoparticles. In addition, the metal nanoparticles 21a are arranged up to the corners of the inner wall of the well 20. In Fig. 2(b), the metal layer is a metal plating layer 22, which is uniformly arranged up to the corners of the inner wall of the well 20.

[0029] (Well plate) The well plate may be a publicly known or commonly used microwell plate. The number of wells (holes) in the well plate is not particularly limited, but may be 6, 24, 96, or 384 wells. Among these, 96 or 384 wells are preferred from the viewpoint of simultaneously detecting a small amount and a large number of analytes.

[0030] The material of the well plate is not particularly limited, and examples thereof include resins (plastics) such as synthetic polymers and natural polymers, rubber, glass, ceramics, metals, wood, paper, etc. Among these, from the viewpoint of ease of forming the metal layer on the well inner wall surface, the material of the well inner wall surface is preferably resin, glass, or paper.

[0031] (metal layer) The metal layer is formed from a plurality of metal nanoparticles, and the plurality of metal nanoparticles are arranged in a manner capable of exerting surface plasmon resonance or surface plasmon coupling, or a metal plating layer is formed. Only one type of the metal nanoparticles may be used, or two or more types may be used.

[0032] The metal elements constituting the metal layer and the metal nanoparticles are not particularly limited, and examples thereof include gold, silver, platinum, palladium, copper, nickel, iron, titanium, zinc, aluminum, tungsten, zirconia, and tin. The metal layer may be composed of a metal alone or a metal compound such as a metal oxide. Among these, gold, silver, platinum, palladium, and copper are preferred. In this specification, for example, the term "gold nanoparticles" refers to a concept including not only nanoparticles composed of gold alone, but also nanoparticles containing gold compounds. The metal layer and the metal nanoparticles may contain one type of metal element, or may contain two or more types of metal elements.

[0033] In this specification, metal nanoparticles refer to metal particles having a size on the order of nanometers, which includes a range of one to several hundred nanometers, and typically has a particle size in the range of 1 to 100 nm.

[0034] The average particle size (median size, D50) of the metal nanoparticles is not particularly limited, but is preferably 1 to 100 nm, more preferably 1 to 50 nm. When the average particle size is within the above range, the effect of enhancing reflected light, scattered light, and fluorescence is more excellent. The average particle size is a value calculated by number averaging, and can be measured, for example, using the device described in the Examples.

[0035] When the zeta potential or charge of the substance to be detected is negative, the zeta potential of the metal nanoparticles is preferably negative, more preferably −50 to −5 mV, and even more preferably −40 to −10 mV, from the viewpoint of suppressing non-specific adsorption.

[0036] The amount of the metal nanoparticles in one well of the well plate is 1 μg / cm 2 It is preferable that the concentration is equal to or higher than 2 μg / cm 2 More preferably, 4 μg / cm 2 The amount of the metal nanoparticles is 1 μg / cm 2 When the amount of the metal nanoparticles is 10 μg / cm or more, the effect of enhancing the optical properties due to the metal nanoparticles can be more highly obtained. 2 It is preferable that the concentration is less than 8 μg / cm 2 The amount of the metal nanoparticles can be adjusted by the amount of the metal nanoparticles in the dispersion liquid described below.

[0037] The metal layer may have at least a part of its surface exposed. In this case, it is preferable that the entire surface is exposed in order to obtain a higher effect of enhancing the optical properties.

[0038] In addition, the metal layer may have a functional group or a binding site that can form a bond with the analyte introduced therein. The functional group or binding site is appropriately selected according to the analyte, and examples thereof include functional groups such as hydroxyl groups, amino groups, carboxyl groups, thiol groups, epoxy groups, succinimide, linear or branched aliphatic hydrocarbon groups, alicyclic hydrocarbon groups, aromatic hydrocarbon groups, and the like; or specific binding substances such as single-stranded DNA, RNA, aptamers, nucleic acids, antibodies, antigens, enzymes, proteins, and resins. The functional group or binding site can be introduced into the metal layer by treating the surface of the metal layer with a compound having a site that can form a bond with the metal and the functional group or binding site. The functional group or binding site may be of only one type, or may be of two or more types.

[0039] When the metal layer has the functional group or binding site, the functional group or binding site is introduced in such a manner that the metal layer can exhibit the surface plasmon resonance or surface plasmon coupling effect. For example, the resin may be a resin layer having a detection site capable of detecting an object to be detected (but only if the resin does not inhibit the surface plasmon resonance or surface plasmon coupling effect of the metal layer). The resin layer may be a single layer or multiple layers.

[0040] The resin layer having a detection site capable of detecting the above-mentioned substance to be detected is preferably a transparent resin layer (particularly a colorless transparent resin layer) from the viewpoint of not inhibiting the surface plasmon resonance or surface plasmon coupling effect of the above-mentioned metal layer. The sensor having the above-mentioned resin layer can be tailor-made according to the substance to be detected, and a sensor capable of selectively detecting the substance to be detected can be quickly and easily produced.

[0041] The type and shape of the resin constituting the resin layer can be appropriately set according to the type of sensitivity to the object to be detected and the desired external stimulus. The resin layer may be formed on a flat surface or a curved surface. The resin layer may be a single layer or multiple layers.

[0042] From the viewpoint of being able to detect the entire analyte, the detection site preferably comprises a spontaneously binding three-dimensional template that is complementary to the three-dimensional structure of the analyte. In addition, when the analyte is a microorganism, the detection site may have a structure that comprises a protein or aptamer, such as a lectin or antibody, that specifically binds to a sugar chain, antigen, or protein present on the surface of the analyte.

[0043] An embodiment of the sensor of the present invention having a detection site capable of detecting the above-mentioned object to be detected is shown in Figs. 3 and 4. The sensor shown in Fig. 3 is composed of a metal nanoparticle layer 21 composed of a plurality of metal nanoparticles 21a arranged on the surface of the inner wall 20a of the well 20, and a resin layer 30 provided on the surface of the metal nanoparticle layer 21. The resin layer 30 is formed so as to cover the plurality of metal nanoparticles 21a collectively. The resin layer 30 may cover the plurality of metal nanoparticles 21a individually, and the metal nanoparticle layer may be a metal plating layer. The resin layer 30 has a detection site 31 which is a hole having a three-dimensional structure formed according to the object to be detected. Fig. 3 shows a state in which the object to be detected has been released, and Fig. 4 shows a state in which the object to be detected 40 has been taken into the detection site 31 of the resin layer 30.

[0044] The resin layer is preferably capable of attaching and detaching the object to be detected by an external stimulus. The external stimulus may be a change in an electric field, temperature, pH, light, chemical reaction, or the like. The variability of the resin layer due to an external stimulus depends on the type of resin constituting the resin layer. As a resin having such variability, a known or commonly used resin having an external stimulus may be used.

[0045] The thickness of the resin layer is not particularly limited, but is preferably 1000 nm or less, more preferably less than 500 nm, and even more preferably 300 nm or less. When the thickness of the resin layer is 1000 nm or less, it is possible to more effectively exert the surface plasmon resonance and surface plasmon coupling effects. In addition, the thickness of the resin layer is preferably 1 nm or more in a state where it functions as a sensor (for example, in the case of a phase-transitionable resin layer, in a state where it is possible to incorporate the object to be detected) from the viewpoint of being able to sufficiently incorporate the object to be detected.

[0046] From the viewpoint of being able to easily form a resin layer on the surface of a metal layer (particularly a gold layer) and being able to form a resin layer having temperature and pH sensitivity, it is preferable that the resin constituting the resin layer contains a constituent unit derived from a hydrocarbon group-containing (meth)acrylamide as a main constituent unit. Since the hydrocarbon group-containing (meth)acrylamide has an amide group, which is a polar group, and a hydrocarbon group, which is a hydrophobic group, the resin has excellent dispersibility in water in a low-temperature environment, and when heated, the resin shrinks, aggregates, gels, etc. due to hydrophobic interactions, thereby exhibiting temperature sensitivity and also pH sensitivity. Therefore, the resin layer can undergo phase transition due to temperature fluctuations and pH fluctuations. For example, in a low-temperature environment, the resin layer 30 is in an expanded state as shown in FIG. 4, and the detection target 40 can be taken into the detection site 31. Then, when heated, it is presumed that the structure of the detection site 31 is not maintained because the resin layer 30 shrinks as shown in FIG. 5, and the detection target 40 is discharged (desorbed / detached) from the detection site 31. When the sensor is to be used again, the resin layer 30 can be expanded by placing it in a low-temperature environment, and the structure of the detection site 31 can be restored. In this way, the substance to be detected can be intentionally released after it is detected, and the three-dimensional structure can be restored and reused as a sensor. The resin layer, which is made of a resin containing a structural unit derived from a hydrocarbon group-containing (meth)acrylamide as a main structural unit, can be formed as a single layer, and the thickness of the resin layer can be formed relatively thin, for example, less than 500 nm, so that the characteristics of the base material, such as magnetism, optical properties, conductivity, and electrical responsiveness, can be fully exhibited.

[0047] The number of carbon atoms of the hydrocarbon group in the above-mentioned hydrocarbon group-containing (meth)acrylamide is preferably 6 or less, more preferably 4 or less, in consideration of the balance with the hydrophilicity of the resin due to the amide group, which is a polar group. In addition, the above-mentioned hydrocarbon group is preferably a branched hydrocarbon group, from the viewpoint of more easily causing shrinkage and aggregation of the resin due to steric hindrance in the resin, and from the viewpoint of easily forming a detection site with a three-dimensional structure according to the object to be detected. For this reason, among the above-mentioned hydrocarbon group-containing (meth)acrylamide, N-isopropyl(meth)acrylamide and Nt-butyl(meth)acrylamide are preferable. The above-mentioned hydrocarbon group-containing (meth)acrylamide may be one type or two or more types. In this specification, "(meth)acryl" refers to acrylic or methacrylic.

[0048] The resin constituting the resin layer may contain a constituent unit derived from another polymerizable monomer copolymerizable with the hydrocarbon group-containing (meth)acrylamide depending on the type of the object to be detected. As the other polymerizable monomer, for example, from the viewpoint of easily forming a resin layer having a detection site according to the type of the object to be detected, a polymerizable monomer (polar group-containing monomer) containing a polar group such as a carboxy group, an acid anhydride group, a hydroxyl group, an epoxy group, a sulfonic acid group, a phosphoric acid group, or a nitrogen atom-containing group is preferable.

[0049] Examples of the monomer having a carboxy group (carboxy group-containing monomer) include acrylic acid, methacrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, citraconic acid, etc. Examples of the monomer having an acid anhydride group (acid anhydride group-containing monomer) include maleic anhydride, itaconic anhydride, etc.

[0050] The resin constituting the resin layer may have a structural part derived from a polymerization initiator, a crosslinking agent, a chain transfer agent, etc. The crosslinking agent may be a multifunctional compound, which is appropriately selected according to the type of the polar group-containing monomer used as the polymerizable monomer. Among them, a multifunctional imide-based compound is preferred from the viewpoint of excellent dispersibility in water and reactivity with a carboxyl group.

[0051] When the resin constituting the resin layer is a copolymer, it may be any of a random copolymer, a block copolymer, a graft copolymer, and the like.

[0052] The metal layer may be insulating, and has a resistance of, for example, 0.3 MΩ / mm or more, preferably 1 MΩ / mm or more, and more preferably 1 GΩ / mm or more. If the metal layer is insulating, it is presumed that the distance between the metal nanoparticles is appropriate, and from the viewpoint of surface plasmon coupling, the effect of enhancing scattered light and fluorescence by the metal nanoparticles can be more highly obtained. The resistance value of the metal layer may be 100 Ω / mm or less. If the resistance value of the metal layer is 100 Ω / mm or less and is conductive, it is presumed that the gaps disappear due to the growth of the metal nanoparticles, and a uniform metal plating layer having a film thickness (1 to 100 nm) based on the particle size of the metal nanoparticles is formed. When incident light is irradiated onto the metal plating layer from the substrate surface, if the critical angle is exceeded, the incident light is totally reflected, an evanescent wave is generated on the surface of the metal plating layer, and surface plasmon is generated. Detection is possible using the change in reflectance based on this surface plasmon.

[0053] When the metal layer is the metal nanoparticle layer, the distance between the metal nanoparticles in the metal nanoparticle layer is preferably not more than twice the diameter of the metal nanoparticles, more preferably 2 to 200 nm, and even more preferably 10 to 100 nm, from the viewpoint of better exerting the surface plasmon resonance or surface plasmon coupling effect.

[0054] The sensor of the present invention is a sensor for detecting an object to be detected. The object to be detected may be a microorganism or a molecule. The microorganism may be, for example, a virus, a bacterium, a fungus, or a protozoan. The virus may be, for example, an influenza virus, a hepatitis A virus, an adenovirus, a rotavirus, a norovirus, or a coronavirus. Examples of the bacteria include Escherichia genus such as Escherichia coli, Pseudomonas genus such as Pseudomonas aeruginosa, Acinetobacter genus such as Acinetobacter calcoaceticus, Serratia genus, Klebsiella genus, Enterobacter genus, Citrobacter genus, Burkholderia genus, Sphingomonadase genus, Chromobacterium genus, Salmonella genus, Vibrio genus, Legionella genus, Campylobacter genus, Yersinia genus, Proteus genus, Neisseria genus, Staphylococcus genus, Streptococcus genus, Enterococcus genus, Clostridium genus, Corynebacterium genus, Listeria genus, Bacillus genus, Mycobacterium genus, Chlamydia genus, Rickettsia genus, Haemophilus genus, etc. Examples of the fungi include fungi such as Candida, etc. Examples of the protozoa include Cryptosporidium, etc. The above molecules include amino acids, organic acids, sugars, peptides, DNA, RNA, proteins, antigens, toxins, drugs, and the like.

[0055] In particular, the analyte preferably has optical properties such as fluorescence properties and light absorption properties, from the viewpoint of being able to detect the incorporation of the analyte into the sensor of the present invention. In addition, if the analyte does not have the optical properties or has weak optical properties, it may be labeled with a molecule having optical properties, or the analyte may be detected by utilizing the fact that the analyte adheres to the surface of the metal layer due to binding of the functional group or binding site with the analyte, and the reflectance of the metal layer surface changes.

[0056] In the sensor of the present invention, for example, a sample (solution) containing an analyte is introduced into a well of a well plate, and the analyte having a functional group or binding site introduced into the metal layer, or a site capable of binding with the specific binding substance, forms a bond with the functional group, binding site, or specific binding substance, and / or, if the sample (solution) contains an antibody, the analyte adheres to the metal layer surface via the antibody. When both are used, the analyte is sandwiched between the functional group, binding site, or specific binding substance and the antibody, and adheres to the metal layer surface. The responsiveness of the analyte or labeling substance can be enhanced as a characteristic of the metal nanoparticles, and the analyte can be detected. For example, when the analyte or labeling substance is a fluorescent substance, the fluorescence emitted by the substance incorporated into the sensor of the present invention can be enhanced, and the analyte can be detected using the enhanced fluorescence as a label. When the analyte is not a fluorescent substance, the sample (solution) is mixed with a conjugate of a fluorescent substance and an antibody together with the analyte, thereby enhancing the fluorescence emitted by the fluorescent substance when the analyte is taken into the sensor of the present invention, and the analyte can be detected using the enhanced fluorescence as a label. Furthermore, since the sensor of the present invention can enhance the responsiveness of the analyte or the labeling substance in this way, the steps of culturing and concentrating the analyte can be shortened or omitted, and minute analytes can be detected quickly and simply. Furthermore, the sensor of the present invention has excellent environmental stability because it can be recovered and reused.

[0057] [Sensor manufacturing method] A method for manufacturing the sensor of the present invention will be described. The sensor of the present invention having a metal nanoparticle layer formed by adhering metal nanoparticles can be manufactured by a manufacturing method including a step of depositing a solution containing an organic binder having a site capable of forming a bond with the material of the well inner wall surface and a site capable of forming a bond with the metal constituting the metal nanoparticle layer into a well of a well plate to adhere the organic binder to the well inner wall surface (organic binder adhering step), and a step of depositing a dispersion containing metal nanoparticles constituting the metal nanoparticle layer into the well to adhere the metal nanoparticles to the well inner wall to form a metal nanoparticle layer (metal nanoparticle layer forming step). In addition, when a well plate having a site capable of forming a bond with the metal constituting the metal nanoparticle layer on the well inner wall surface is used, the organic binder adhering step can be omitted. In addition, the sensor of the present invention having a metal plating layer can be manufactured by a manufacturing method further including a step of growing the metal nanoparticles in the metal nanoparticle layer after the metal nanoparticle layer forming step.

[0058] (Organic binder attachment process) The site of the organic binder capable of forming a bond with the material of the well inner wall surface is appropriately selected according to the type of material forming the well inner wall. When the material is plastic or resin, examples of the site capable of forming a bond with the material of the well inner wall surface include linear or branched aliphatic hydrocarbon groups, alicyclic hydrocarbon groups, aromatic hydrocarbon groups, and other hydrocarbon groups. The hydrocarbon groups may have a substituent such as a hydroxyl group, a carboxyl group, an amino group, a thiol group, or an epoxy group. The site may have only one type, or may have two or more types.

[0059] Examples of the moiety in the organic binder that can form a bond with the metal constituting the metal nanoparticle layer include a thiol group, a disulfide group, an amino group, an imino group, a carboxy group, a hydroxy group, etc. The organic binder may have only one type of moiety or two or more types of moieties.

[0060] (Metal nanoparticle layer formation process) The dispersion liquid can be prepared by stirring the salt or complex of the metal constituting the metal nanoparticle layer in a solvent, heating it as necessary, in the presence of a reducing agent. Examples of the reducing agent include citrate, ascorbate, sodium borohydride, hydrazine, hypophosphite, and EDTA. An acid or alkali may also be added as a pH adjuster.

[0061] The above metal salts or the above metal complexes may be used either alone or in combination. The above metal salts or the above metal complexes may be used either alone or in combination.

[0062] The metal (metal element) in the metal salt or the metal complex is the same as the metal (metal element) constituting the metal nanoparticle layer. Examples of the metal in the metal salt or the metal complex include gold, silver, platinum, palladium, copper, nickel, iron, titanium, zinc, tungsten, zirconia, aluminum, and tin.

[0063] Examples of silver salts include silver nitrate, silver sulfate, silver chloride, silver oxide, silver acetate, silver nitrite, silver chlorate, and silver sulfide. Examples of gold salts include chloroauric acid, potassium gold chloride, and sodium gold chloride. Examples of platinum salts include chloroplatinic acid, platinum chloride, platinum oxide, and potassium chloroplatinate. Examples of palladium salts include palladium nitrate, palladium acetate, palladium chloride, palladium oxide, and palladium sulfate. Examples of copper salts include copper nitrate, copper acetate, copper sulfate, copper formate, copper fumarate, copper chloride, and copper bromide. Examples of iron salts include iron oxide, iron chloride, iron bromide, iron iodide, iron acetate, and iron stearate. Examples of titanium salts include titanium oxide, titanium sulfate, titanium nitrate, titanium chloride, titanium fluoride, and lithium titanate. Examples of aluminum salts include aluminum nitrate and aluminum chloride. Examples of zinc salts include zinc chloride and zinc sulfate. Examples of tin salts include tin sulfate and stannic chloride. Examples of tungsten salts include sodium tungstate, potassium tungstate, calcium tungstate, lithium tungstate, magnesium tungstate, silver tungstate, cerium tungstate, cobalt tungstate, tungstic acid, ammonium tungstate, tungsten carbonyl, etc. Examples of zirconium salts include zirconium acetate, zirconium nitrate, zirconium sulfate, zirconium oxide, etc.

[0064] The ligand in the above metal complex is, for example, NH 3 , RNH 2 , halogen atoms (Cl, F, Br, I, At), carboxy group, carboxylate group (-CO-O-), pyridyl group, H 2 O, CO 3 2- , O.H. - , NO 2 - , NO 3 - , NO 3 2- , S.O. 3 2- , R.O.H., N. 2 H 4 , P.O. 43- , R 2 O, R.O. - , R.O.P. 3 2- , (RO) 2 PO 2 - , R 2 S, R 3 P, R.S. - , C.N. - , R.S.H., R.N.C., (R.S.) 2 PO 2 - , (RO) 2 P(O)S - , SCN - , CO, H - , N 3 - , imidazole ring, unsaturated cyclic organic group, R - (wherein each of the above "R"s represents a saturated or unsaturated organic group.) It should be noted that there are compounds that correspond to both the above metal salts and the above metal complexes.

[0065] The dispersion liquid prepared as described above contains metal nanoparticles. The average particle size of the metal nanoparticles in the dispersion liquid is the average particle size of the metal nanoparticles in the metal nanoparticle layer. The average particle size of the metal nanoparticles can be adjusted by the type and amount of the metal salt or metal complex.

[0066] The content of the metal nanoparticles in the dispersion is, for example, 0.001 to 0.05% by mass relative to the total amount (100% by mass) of the dispersion. The temperature for heating in preparing the dispersion is, for example, 60 to 100° C. The temperature for cooling is, for example, 5 to 10° C. As the solvent, water is preferable from the viewpoint of having little effect on the object to be detected.

[0067] (growth process) The growth step can be carried out by pouring the dispersion liquid containing metal nanoparticles used to form the metal nanoparticle layer into the well in which the metal nanoparticle layer is formed and stirring it. As a result, the metal nanoparticles in the dispersion liquid can be attached to the surface of the metal nanoparticles constituting the metal nanoparticle layer in the well, thereby growing the metal nanoparticles constituting the metal nanoparticle layer. Alternatively, the metal salt or metal complex in the dispersion liquid is reduced using the metal nanoparticles constituting the metal nanoparticle layer in the well as nuclei and precipitates as metal, thereby increasing the particle size of the metal nanoparticles constituting the metal nanoparticle layer, thereby growing the metal nanoparticles constituting the metal nanoparticle layer. As a result, the metal plating layer can be formed. The dispersion liquid used in the growth step may be the same as or different from the dispersion liquid used in the metal nanoparticle layer formation step. For example, the metal salt or metal complex for preparing the dispersion liquid may be the same as or different from the metal nanoparticle layer formation step and the growth step.

[0068] After the metal nanoparticle layer forming step or the growing step, the method may include a step of washing the inside of the well with ultrapure water (washing step), a step of introducing a functional group capable of forming a bond with an analyte to the surface of the metal nanoparticle layer or metal plating layer (functional group introduction step), and a step of introducing the specific binding substance to the surface of the metal layer (specific binding substance introduction step). When the specific binding substance is the resin layer, the specific binding substance introduction step may include a polymerization step of a polymerizable monomer that forms the resin layer.

[0069] (Functional group introduction step) In the functional group introduction step, for example, a solution (such as an aqueous solution) containing a compound having a site capable of forming a bond with an analyte, such as a biotin derivative having a thiol group, and a site capable of forming a bond with a metal in a metal nanoparticle is poured into the well in which the metal layer is formed and allowed to stand. After that, the inside of the well may be washed with ultrapure water.

[0070] In this manner, the sensor of the present invention can be manufactured. EXAMPLES

[0071] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0072] (evaluation) Average particle size and zeta potential of metal nanoparticles: Measured using a zeta potential / particle size measurement system (product name "ELSZ-2Plus", manufactured by Otsuka Electronics Co., Ltd.). Absorption spectra of dispersions and suspensions: Measured using an ultraviolet-visible spectrophotometer (product name "UV-3100PC", manufactured by Shimadzu Corporation). Absorption and fluorescence spectra of the well plate: were measured using a plate reader (product name "ARVO X3", manufactured by PerkinElmer).

[0073] Manufacturing Example 1 (Preparation of 30 nm gold nanoparticles) 563 μL of 2% by mass sodium citrate aqueous solution was added to 25 mL of ultrapure water and heated to 80° C. 750 μL of 1% by mass chloroauric acid aqueous solution was added to the above aqueous solution while stirring, and stirring was continued for 20 minutes. In this way, a gold nanoparticle dispersion (concentration: 0.014% by mass, average particle size: 34.4±7.1 nm, zeta potential: -35 mV) was prepared.

[0074] Manufacturing Example 2 (Preparation of 30 nm silver nanoparticles) 1.2 mg of EDTA·2Na and 50 μL of 0.1 M silver nitrate solution were added to 20 mL of ultrapure water and heated to 100°C. 736 μL of 0.1 M sodium hydroxide solution was added to the above solution while stirring vigorously, and stirring was continued for 5 minutes. In this way, a silver nanoparticle dispersion (concentration: 0.0027 mass%, average particle size: 30.1 ± 6.1 nm, zeta potential: -37 mV) was prepared.

[0075] Production Example 3 (Preparation of 2 nm silver nanoparticles) 50 mL of an aqueous solution of 1 mM sodium borohydride and 0.3 mM sodium citrate was prepared. 50 μL of 0.1 M silver nitrate aqueous solution was added to the above aqueous solution while vigorously stirring, and the stirring was continued for 10 minutes at 5° C. In this way, a silver nanoparticle dispersion (concentration: 0.0011% by mass, average particle size: 2.0±0.2 nm, zeta potential: -29 mV) was prepared.

[0076] Production Example 4 (Preparation of 40 nm palladium nanoparticles) 750μL of 1% by mass palladium chloride and 1.7M hydrochloric acid aqueous solution were added to 25mL of ultrapure water and heated to 80℃. 1mL of 2% by mass sodium citrate aqueous solution and 400μL of 2% by mass sodium ascorbate aqueous solution were added to the above aqueous solution while stirring, and stirring was continued for 20 minutes. In this way, a palladium nanoparticle dispersion (concentration: 0.017% by mass, average particle size: 37.6±9.3nm, zeta potential: -30mV) was prepared.

[0077] Reference example 1 (Fluorescence enhancement of metal nanoparticles in aqueous solution) Hydrochloric acid was added to the gold nanoparticle dispersion liquid prepared in Production Example 1 and the silver nanoparticle dispersion liquid prepared in Production Example 2, respectively, to adjust the pH to 7. Then, the gold nanoparticle dispersion liquid with the adjusted pH was dropped into 3 mL of 1 μM fluorescein aqueous solution, and the fluorescence spectrum was measured. The results are shown in FIG. 6(a). The silver nanoparticle dispersion liquid with the adjusted pH was also dropped into 3 mL of 1 μM fluorescein aqueous solution, and the fluorescence spectrum was measured. The results are shown in FIG. 6(b). The amounts of gold nanoparticles and silver nanoparticles added were 0 μg, 0.5 μg, 1.0 μg, and 1.6 μg, respectively. As a result, for both gold nanoparticles and silver nanoparticles, the fluorescence was enhanced with an increase in the amount of metal nanoparticles added. Among them, the enhancement effect was more pronounced for silver nanoparticles.

[0078] Example 1 (Immobilization of metal nanoparticles onto 96-well plates) Hydrochloric acid was added to each of the metal nanoparticle dispersions prepared in Production Examples 1 to 4 to adjust the pH to 4. Then, 400 μL of the pH-adjusted dispersion was added to each well of a 96-well well (ELISA amino plate "MS-8696F", manufactured by Sumitomo Bakelite Co., Ltd.) whose inner wall was modified with an amino group, and the well was left to stand for 12 hours. After that, the dispersion was removed, and the inner wall of the well was thoroughly washed with ultrapure water. In this way, a sensor was prepared in which a metal nanoparticle layer was formed on the inner wall surface of the well (6.4 μg of immobilization on the inner wall of the well). A top view photograph of the sensor is shown in FIG. 7. Also, a scanning electron microscope (SEM) image of the metal nanoparticle layer formed on the inner wall surface of the well is shown in FIG. 8. FIG. 8(a) is an image at a magnification of 20,000 times, and FIG. 8(b) is an image at a magnification of 100,000 times. From the SEM images, the distance between the metal nanoparticles in the metal nanoparticle layer was measured to be within the range of 10 to 100 nm.

[0079] Example 2 (Evaluation of the amount of silver nanoparticles (30 nm) immobilized on the inner wall of the well) In the same manner as in Production Example 2, 10 kinds of silver nanoparticle dispersions were prepared with concentrations ranging from 0.00027% by mass to 0.0027% by mass at equal intervals. Then, 400 μL of the above 10 kinds of pH-adjusted dispersions were added to a 96-well well (ELISA amino plate "MS-8696F", manufactured by Sumitomo Bakelite Co., Ltd.) whose inner wall was modified with an amino group, and the well was left to stand for 12 hours. After that, the dispersion was removed, and the inner wall of the well was thoroughly washed with ultrapure water. In this way, a sensor in which silver nanoparticles were immobilized on the inner wall surface of the well was prepared. A top view photograph of the prepared sensor is shown in FIG. 9. In FIG. 9, the left end is a well in which silver nanoparticles were immobilized using the dispersion with the lowest concentration, and the right end is a well in which dispersions with increasing concentrations were used. Then, the absorption spectrum of the silver nanoparticle dispersion (concentration 0.0027% by mass) and the UV-vis absorption spectrum of the well after immobilization of silver nanoparticles using the dispersion were measured. The results are shown in FIG. 10(a).

[0080] As shown in Figure 10(a), the silver nanoparticle dispersion showed an absorption peak at 406.5 nm. After the silver nanoparticles were immobilized in the well, the absorbance was greatly reduced, but there was no change in the maximum absorption wavelength. Therefore, by utilizing the fact that absorbance and concentration are proportional to each other according to the Beer-Lambert law (A=ε|c), the amount of immobilization in the well was estimated by calculating the difference in silver nanoparticle concentration in the dispersion from the difference in absorbance (at 406.5 nm) of the dispersion before and after immobilization. The relationship between the concentration of the dispersion and the amount of immobilized silver nanoparticles immobilized on the inner wall of the well is shown in Figure 10(b). As shown in Figure 10(b), the concentration of the dispersion used for immobilization and the amount of immobilized silver nanoparticles showed a good proportional relationship. If the amount of immobilization is n (μg) and the concentration of the dispersion used for immobilization is c (mass%), the approximation formula is n = (3.600 × 10 -3 )c(R 2 =0.99) The immobilized amount was maximum at 9.6 μg when the dispersion liquid concentration was 0.0027% by mass.

[0081] Example 3 (Optical property evaluation of metal nanoparticle immobilized wells) Using a fiber optic spectrometer, the absorption spectrum of the bottom surface of the well where silver nanoparticles were immobilized in the sensor prepared in Example 2 (FIG. 11(a)) and the absorption spectrum of the bottom surface of the well where gold nanoparticles were immobilized in the sensor prepared in Example 1 (FIG. 11(b)) were measured. In addition, the absorbance of the well where silver nanoparticles were immobilized was measured at a wavelength of 410 nm using a plate reader (FIG. 11(c)).

[0082] As shown in Fig. 11(a), the silver nanoparticle-immobilized well showed an absorption peak at 410 nm. This indicates that the silver nanoparticles were adsorbed to the well in a dispersed state. In addition, as shown in Fig. 11(c), when the absorption peak at 410 nm was plotted against the immobilization amount, the absorbance also increased with an increase in the immobilization amount. This increase in absorbance became gentler after the immobilization amount of 4.4 μg. The absorption spectrum shows that as the immobilization amount increases, a new absorption peak appears around 500 nm in addition to 410 nm. This is thought to be due to plasmon coupling caused by the closer interparticle distance. As shown in Fig. 11(b), in the gold nanoparticle-immobilized well, in addition to the absorption peak around 530 nm that is typical of dispersed gold nanoparticles, an absorption peak thought to be due to plasmon coupling was confirmed at 650 nm to 700 nm.

[0083] Example 4 (Comparison of the fluorescence enhancement effect of various metal nanoparticle immobilized wells) 40 μL of 10 μM fluorescein solution was added to each of the various metal nanoparticle-immobilized wells in the sensor prepared in Example 1, and the water was evaporated by leaving it in a dark room for 12 hours, and 400 pmol of fluorescein was deposited on the bottom of the well. Then, the fluorescence intensity of each well and a well to which metal nanoparticles were not immobilized was measured using a plate reader (excitation wavelength: 490 nm, measurement wavelength: 535 nm) (FIG. 12(a)). In addition, the relationship between the immobilization amount and the fluorescence enhancement effect was investigated for wells to which silver nanoparticles with an average particle diameter of 30 nm were immobilized (FIG. 12(b)).

[0084] As shown in FIG. 12(a), the wells immobilized with silver nanoparticles exhibited a remarkable fluorescence enhancement effect. In particular, those with an average particle diameter of 30 nm showed a fluorescence intensity 20 times or more higher than that of wells without particles immobilized. In addition, wells immobilized with gold nanoparticles and palladium nanoparticles also exhibited a fluorescence enhancement effect, which was about two and three times higher, respectively, compared to wells without particles immobilized. In addition, as shown in FIG. 12(b), for silver nanoparticles with an average particle diameter of 30 nm, the fluorescence enhancement effect also increased with an increase in the immobilized amount. This increase in fluorescence intensity became even more remarkable after the immobilized amount was 4.4 μg. Therefore, as described above, it is shown that as the immobilized amount of metal nanoparticles increases, the absorption spectrum of the wells shows an absorption peak due to plasmon coupling. From this, it is considered that this plasmon coupling makes the fluorescence enhancement effect more remarkable.

[0085] Example 5 (Application of metal nanoparticle immobilized wells to bioanalysis) Binding of avidin to metal nanoparticle-immobilized wells To the immobilization wells (immobilization amount 9.6 μg) using silver nanoparticles (30 nm) and gold nanoparticles (30 nm) prepared in Example 1, 400 μL of 250 μM thiol group-introduced biotin aqueous solution was added and left to stand for 2 hours. After that, the aqueous solution was removed, and the wells were thoroughly washed with ultrapure water, and then 400 μL of a fluorescein-labeled streptavidin aqueous solution of a predetermined concentration was added and left to stand for 2 hours. Then, the aqueous solution was removed, and the wells were thoroughly washed with ultrapure water, and the fluorescence intensity was measured using a plate reader (excitation wavelength: 490 nm, measurement wavelength: 535 nm).

[0086] Binding of avidin to amino plates for ELISA A 2% by mass glutaraldehyde aqueous solution was prepared using 0.2 mM phosphate buffer (pH 9). 400 μL of the above aqueous solution was added to a well of an ELISA amino plate and left to stand at 37° C. for 2 hours. The aqueous solution was then removed, and the plate was thoroughly washed with ultrapure water, after which 400 μL of a fluorescein-labeled streptavidin aqueous solution of a given concentration was added and left to stand for 2 hours. The aqueous solution was then removed, and the plate was thoroughly washed with ultrapure water, after which the fluorescence intensity was measured using a plate reader (excitation wavelength: 490 nm, measurement wavelength: 535 nm).

[0087] The change in fluorescence intensity measured above versus the amount of avidin is shown in Figures 13(a) to (c). Black circles (●) indicate the cases where silver nanoparticle-immobilized wells were used, and black squares (■) indicate the cases where gold nanoparticle-immobilized wells were used. Figure 13(b) is an enlarged view of the fluorescence intensity of 0 to 2000 in Figure 13(a). Figure 13(c) is a graph showing the change in fluorescence intensity at avidin amounts of 0 to 25 pmol. As shown in Figures 13(a) to (c), the silver nanoparticle-immobilized wells significantly increased the fluorescence of fluorescein modified to avidin, and when the amount of avidin was 25 pmol, the fluorescence intensity was more than 10 times that of the amino plate for ELISA. When the amino plate for ELISA was used, the fluorescence intensity was 10 times higher than that of the amino plate for ELISA. -1 Although avidin could not be detected on the pmol scale, the use of silver nanoparticle-immobilized wells enabled the fluorescence detection of avidin on this scale. As shown in Figure 13(c), the silver nanoparticle-immobilized wells showed good quantification in the range of avidin amounts from 2.5 pmol to 25 pmol.

[0088] Example 6 (Conductivity evaluation) Preparation of gold plating layer 100 μL of ultrapure water, 150 μL of 1 mass% chloroauric acid aqueous solution, and 150 μL of 0.1 M hydroxylamine hydrochloride aqueous solution were added in this order to the gold nanoparticle-immobilized well of the sensor prepared in Example 1. After the hydroxylamine hydrochloride aqueous solution was added, the mixture was quickly stirred by pipetting and allowed to stand for 12 hours. The aqueous solution was then removed, and the inner wall of the well was thoroughly washed with ultrapure water. In this way, a gold plating layer was formed on the inner wall of the well. A top view photograph of the sensor with the gold plating layer formed is shown in FIG. 14.

[0089] Preparation of silver plating layer 124 μL of ultrapure water, 150 μL of 0.1 M silver nitrate aqueous solution, 120 μL of 5 mass% Rochelle salt aqueous solution, and 6 μL of ethylenediamine were added in this order to the silver nanoparticle-immobilized well of the sensor prepared in Example 1. After the addition of ethylenediamine, the mixture was quickly stirred by pipetting and allowed to stand for 12 hours. Thereafter, the aqueous solution was removed, and the inner wall of the well was thoroughly washed with ultrapure water. In this way, a silver plating layer was formed on the inner wall of the well. A top view photograph of the sensor on which the silver plating layer was formed is shown in FIG. 14.

[0090] Preparation of palladium plating layer In the palladium nanoparticle immobilized well of the sensor prepared in Example 1, 0.056 mass% palladium chloride, 242 μL of 1.7 M hydrochloric acid solution, 1.82 μL of ethylenediamine, 1.70 μL of 10 M hydrochloric acid, and 39.4 μL of 5 mass% sodium hypophosphite aqueous solution were added in this order. After adding the sodium hypophosphite aqueous solution, the solution was quickly stirred by pipetting and left to stand for 12 hours. Thereafter, the aqueous solution was removed, and the inner wall of the well was thoroughly washed with ultrapure water. In this way, a palladium plating layer was formed on the inner wall of the well.

[0091] Evaluation of the conductivity of various wells The conductivity was measured for the various metal nanoparticle immobilized wells in the sensor prepared in Example 1, and the wells with gold plating layers, silver plating layers, and palladium plating layers prepared above. The conductivity measurements were performed using a digital multimeter to measure the resistance between the bottom and side surfaces and the resistance between the side surfaces, with the electrode needles spaced 3 mm apart. The results are shown in Table 1.

[0092] [Table 1]

[0093] The amino plate for ELISA was made of polystyrene and therefore showed insulating properties. In addition, the wells with various metal nanoparticles immobilized in the sensor prepared in Example 1 exceeded the measurement limit of 1 GΩ and showed no conductivity. On the other hand, the wells with gold plating layer and wells with silver plating layer prepared above showed good conductivity both between side and side and between bottom and side. The wells with palladium plating layer showed resistance values ​​on the MΩ scale between side and side, and between bottom and side it was 1 GΩ or more. Using various metal nanoparticles, a uniform metal plating layer with a film thickness of 100 nm or less was obtained regardless of conductivity. When incident light is irradiated onto the metal plating layer from the substrate surface, if the critical angle is exceeded, the incident light is totally reflected, evanescent waves are generated on the surface of the metal plating layer, and surface plasmon is generated. This surface plasmon has a resonance angle at which the intensity of the reflected light is minimum, and the resonance angle is specific to the metal plating layer to which the functional groups and binding sites are fixed. The refractive index (dielectric constant) of the surface of the metal plating layer changes due to the binding of the functional groups and binding sites with the above-mentioned analyte, and the resonance angle changes. Since the reflectance changes at a specific angle, the above-mentioned analyte can be quantified, and the reaction occurring on the surface of the metal plating layer can be observed in real time. A thin gold film is useful in that it is easy to introduce the above-mentioned functional groups and binding sites via thiol groups.

[0094] Example 7 (bacteria detection) Fluorescein-labeled antibodies were added to an aqueous solution of E. coli O157:H7 and stirred to bind the fluorescein-labeled antibodies to E. coli O157:H7 cells, and free fluorescein-labeled antibodies were removed. Then, 400 μL of an aqueous solution of fluorescein-labeled E. coli O157:H7 cells at a predetermined concentration was added to the silver nanoparticle (30 nm) immobilized well of the sensor prepared in Example 1 and allowed to stand for 2 hours. Then, the aqueous solution was removed and thoroughly washed with ultrapure water. In this way, a microplate having multiple wells with different numbers of E. coli cells was prepared. Fluorescence intensity measurements were performed on the multiple wells using a plate reader (excitation wavelength: 490 nm, measurement wavelength: 535 nm). The results are shown in Figures 15(a) and (b). Figure 15(b) is an enlarged view of the range of 0 to 2000 E. coli cells in Figure 15(a). The number of adsorbed E. coli cells was counted using a bright-field microscope (product name "EVOS FL Auto", Life Technologies). The micrographs are shown in Figure 16. Figure 16(a) shows a micrograph of the count of the number of adsorbed bacterial cells in the silver nanoparticle-immobilized well, and Figure 16(b) shows a micrograph of the count of the number of adsorbed bacterial cells in the unmodified well.

[0095] Observation under a bright-field microscope revealed that 88±6% of the bacteria were adsorbed to the bottom of the well. The adsorption rate was almost the same as the number of E. coli cells incubated, and the number of cells was 10 3 From 10 7The E. coli cells covered with glycans are adsorbed by multiple hydrogen bonds formed with the carboxyl groups of EDTA covering the silver nanoparticle surface. E. coli cells, which have a negative zeta potential (-20 mV), are also electrically adsorbed to the positively charged bottom of the well. There was no difference in the number of adsorbed cells with or without silver nanoparticles. Thus, as shown in Figure 15(a), the fluorescence enhancement depends on the amount of fluorescein-labeled bacterial cells. And, even though the adsorption rate of cells was almost the same, the fluorescence intensity obtained using the silver nanoparticle-immobilized wells was much higher than that obtained using the unmodified wells. Also, the detection limit of the silver nanoparticle-immobilized wells was significantly improved compared to the unmodified wells, and the detection limit was estimated to be approximately 500 cells, as shown in Figure 15(b).

[0096] Example 8 (bacteria selectivity) The selectivity of bacterial species was examined. S. enterica and E. coli O26 were used as selection targets against E. coli O157. Bacteria adsorption wells were prepared in the same manner as in Example 7, except that S. enterica or E. coli O26 was used instead of E. coli O157. Then, the fluorescence intensity of the microplate having the above-mentioned multiple wells was measured using a plate reader (excitation wavelength: 490 nm, measurement wavelength: 535 nm). Figure 17(a) shows the fluorescence intensity of S. enterica, Figure 17(b) shows the fluorescence intensity of E. coli O26, and Figure 17(c) shows the fluorescence intensity of E. coli O157. The dashed line in Figure 17 shows the fluorescence intensity in the absence of bacteria.

[0097] As shown in FIG. 17, in the absence of fluorescein-labeled antibody, 10 6 The fluorescence intensity was comparable to that of the silver nanoparticle-immobilized wells when the number of bacteria adsorbed increased to 10 7When the bacteria were in the well, the intensity was higher than when there were no bacteria. This is due to the phenomenon of cellular autofluorescence. Although individual bacteria inherently show weak fluorescence, it is thought that the autofluorescence is enhanced when the bacteria are adsorbed to the well and form aggregates. The inner surface area of ​​each well is 2.3 × 10 8 μm 2 The projected area of ​​each cell is estimated to be 1.7 μm 2 Therefore, a single layer of adsorbed cells would theoretically be approximately 10 8 As shown in FIG. 16, the number of cells in the well was 10 6 The cells are uniformly dispersed until the number of adsorbed cells reaches 10 7 In these cases, aggregates are formed and the bacterial autofluorescence intensity per cross-sectional area increases.

[0098] The selectivity of E. coli O157 was examined when it was mixed with other bacteria. First, fluorescein-labeled E. coli O157 was mixed with E. coli O26 cells at 10 5 , 10 6 , and 10 7 Bacteria adsorption wells were prepared in the same manner as in Example 7 using the suspension in the above case. Bacteria adsorption wells were also prepared in the same manner by changing the number of E. coli O157 cells. Then, the fluorescence intensity of the microplate having the above-mentioned multiple wells was measured using a plate reader (excitation wavelength: 490 nm, measurement wavelength: 535 nm). Figure 18 shows the change in fluorescence intensity for each number of E. coli O26 cells mixed. The dashed line in Figure 18 shows the fluorescence intensity in the absence of bacteria.

[0099] As shown in FIG. 18, when the number of E. coli O26 cells was 10 6 The fluorescence intensity in the following cases is consistent with that of E. coli O157 alone. On the other hand, when the number of target E. coli O157 cells is 10 3 In the following, the number of E. coli O26 cells is 10 7When the number of E. coli O157 cells was increased to 10, the background intensity increased. 4 In these cases, the fluorescence intensity again matched that of E. coli O157 alone. Since the amount of fluorescein on the cells was small, it was speculated that the increase in background intensity was due to bacterial autofluorescence. However, if the ratio of fluorescein-labeled E. coli O157 to unlabeled O157 was about 0.10% or more, the source of fluorescence became fluorescein. Therefore, detection of E. coli O157 using silver nanoparticle wells was possible when the number of mixed bacteria in the well was 10 6 Less than this can be achieved directly by fluorescein labeling.

[0100] Example 9 A suspension extracted from spoiled beef was used for the sample analysis. The bacterial species Aeromonas salmonicida and Serratia liquefaciens were found to be mixed in the suspension. The total number of mixed E. coli cells in the well was 1.2 × 10 5 The E. coli O157 analysis was performed at 10 3 ~10 6The measurement was performed on a sample solution in which E. coli O157 cells were added to the above suspension. The above sample solution was mixed with fluorescein-labeled E. coli O157 antibody, and the suspension was then washed to remove unbound fluorescein-labeled E. coli O157 antibody. The resulting suspension was placed in the silver nanoparticle (30 nm) immobilized well prepared in Example 1 and allowed to stand for 2 hours. The aqueous solution was then removed, and the well was thoroughly washed with ultrapure water. In this manner, a microplate was prepared. Then, the number of E. coli O157 cells attached to the silver nanoparticle immobilized well of the above microplate after washing was measured using a plate reader, and the recovery rate and relative standard deviation (RSD) of E. coli O157 were obtained. The recovery rate was calculated from the fluorescence intensity value for the response to E. coli O157 alone. The results are shown in Table 2. As shown in Table 2, the recovery rates [measured cell numbers / input cell numbers] were 100.6–102.4%, and the relative standard deviations (RSDs) were below 4.0% in all cases. These results indicate the feasibility of using silver nanoparticle-immobilized plates in the detection of E. coli O157.

[0101] [Table 2]

[0102] Example 10 (Virus detection) The fluorescein-labeled antibody was added to an influenza virus (H1N1) phosphate buffer solution (pH 7.0) and stirred to bind the fluorescein-labeled antibody to the influenza virus, and the free fluorescein-labeled antibody was removed. Then, 50 μL of an aqueous solution of fluorescein-labeled influenza virus with a predetermined concentration was added to the silver nanoparticle (30 nm) immobilized well prepared in Example 1 and left to stand for 2 hours. Then, the aqueous solution was removed and thoroughly washed with an aqueous phosphate buffer solution (pH 7.0). In this way, a microplate having multiple wells with different numbers of virus particles was prepared. The fluorescence intensity of the multiple wells was measured using a plate reader (excitation wavelength: 490 nm, measurement wavelength: 535 nm). The results are shown in FIG. 19. FIG. 19(a) shows the fluorescence intensity versus virus concentration (μg / mL), and FIG. 19(b) shows the fluorescence intensity versus the number of virus particles (pieces). In FIG. 19, black circles (●) indicate the case where a well with immobilized silver nanoparticles was used, and black squares (■) indicate the case where a well with no immobilized silver nanoparticles was used.

[0103] As shown in Figure 19(a) and (b), the fluorescence enhancement depends on the amount of fluorescein-labeled virus. The fluorescence intensity obtained using the silver nanoparticle-immobilized wells was much higher than that obtained using unmodified wells. Furthermore, the silver nanoparticle-immobilized wells showed significant fluorescence intensity in the concentration range that was not detectable in unmodified wells, with the detection limit being approximately 0.01 μg / mL (3 × 10 3 It was estimated that

[0104] Example 11 (Sandwich method) 100 μL of 1 μg / mL anti-influenza antibody (primary antibody) phosphate buffer solution (pH 7.0) was added to the silver nanoparticle (30 nm) immobilized well of the sensor prepared in Example 1, and the well was left to stand at room temperature for 1 hour, so that the anti-influenza antibody was immobilized in the well. Then, the aqueous solution in the well was removed, and the well was thoroughly washed with 0.02% Tween 20 phosphate buffer solution (pH 7.0). Next, 100 μL of 1% bovine serum albumin phosphate buffer solution (pH 7.0) was added to the well, and the well was left to stand at room temperature for 1 hour, so that the well was blocked. Then, the aqueous solution in the well was removed, and the well was thoroughly washed with 0.02% Tween 20 phosphate buffer solution (pH 7.0). In this way, the anti-influenza antibody and bovine serum albumin were introduced to the surface of the silver nanoparticle layer in the well.

[0105] Then, 100 μL of a phosphate buffer solution (pH 7.0) of influenza virus (H1N1) of a predetermined concentration was added to the well, and the well was left to stand at 37°C for 1 hour to bind with the antibody and selectively bind with the anti-influenza antibody introduced to the surface of the silver nanoparticle layer. Then, the aqueous solution in the well was removed, and the well was thoroughly washed with 0.02% Tween 20 phosphate buffer solution (pH 7.0). Next, 100 μL of 2 μg / mL fluorescein-labeled anti-influenza antibody (secondary antibody) was added to the well, and the well was left to stand at 37°C for 1 hour to bind with the influenza virus (H1N1) selectively bound to the anti-influenza antibody introduced to the surface of the silver nanoparticle layer. Then, the aqueous solution in the well was removed, and the well was thoroughly washed with 0.02% Tween 20 phosphate buffer solution (pH 7.0). After that, the fluorescence intensity of the above-mentioned multiple wells was measured using a plate reader (excitation wavelength: 490 nm, measurement wavelength: 535 nm). The results are shown in FIG. 20. FIG. 20(a) shows the fluorescence intensity versus virus concentration (ng / mL), and FIG. 20(b) shows the fluorescence intensity versus the number of virus particles (particles).

[0106] As shown in Figure 20(a) and (b), the fluorescence enhancement depends on the amount of virus bound to the primary antibody and labeled with fluorescein. By using silver nanoparticle-immobilized wells, a significant fluorescence intensity was obtained in the low concentration range, and the detection limit was estimated to be approximately 0.1 ng / mL (30 particles). [Explanation of symbols]

[0107] 1 Sensor 10-well plate 20 wells 20a Well inner wall 21 Metal nanoparticle layer 21a Metal Nanoparticles 22 Metal plating layer 30 Resin layer 31 Detection site 40 Object to be detected

Claims

1. A sensor for detecting an analyte, comprising: a well plate; and a metal layer having a thickness of 1 to 100 nm formed on an inner wall surface of a well in the well plate and composed of a plurality of metal nanoparticles, the metal layer having a resin layer (which does not inhibit the surface plasmon resonance or surface plasmon coupling effect of the metal layer) equipped with a detection site capable of detecting the analyte, the resin layer being capable of attaching and detaching the analyte in response to an external stimulus, the resin layer being equipped with a spontaneously binding three-dimensional structural template that is complementary to the three-dimensional structure of the analyte.

2. 2. The sensor according to claim 1, which is for simultaneously detecting multiple items related to an analyte, or for simultaneously detecting an analyte in a plurality of samples.

3. The sensor according to claim 1 , wherein the metal layer is a metal nanoparticle layer formed by arranging the plurality of metal nanoparticles or a metal plating layer formed by growing the metal nanoparticles.

4. The sensor according to claim 3 , wherein the metal layer is a metal plating layer, and the metal plating layer is uniformly formed on the inner wall surface of the well.

5. The sensor described in claim 4, wherein the metal plating layer is a layer in which at least some of the gaps between particles have disappeared after the metal nanoparticles have grown.

6. The sensor of claim 3 , wherein the metal layer is the metal nanoparticle layer, and the distance between the metal nanoparticles in the metal nanoparticle layer is 2 to 200 nm.

7. The sensor according to any one of claims 1 to 6, wherein the metal nanoparticles contain one or more metal elements selected from the group consisting of gold, silver, platinum, palladium, copper, nickel, iron, titanium, zinc, aluminum, tungsten, zirconia, and tin, and are composed of a metal element or a metal compound.

8. The sensor according to any one of claims 1 to 7, wherein the average particle size of the metal nanoparticles is 1 to 100 nm.

9. The sensor according to any one of claims 1 to 8, wherein at least a portion of the metal layer is exposed within the well.

10. The sensor according to any one of claims 1 to 9, wherein a specific binding substance is disposed on the metal layer in the well, and the sensor is capable of exerting a surface plasmon resonance or surface plasmon coupling effect.

11. The sensor according to any one of claims 1 to 10, wherein the well plate is a microwell plate.

12. The amount of the metal nanoparticles in one well is 1 μg / cm 2 The sensor according to claim 11 .

13. 13. The sensor according to claim 1, wherein the surface resistance value of the metal layer in one well is 0.3 MΩ / mm or more.

14. A sensor described in any one of claims 1 to 12, wherein the resistance value of the metal layer is 100 Ω / mm or less.

15. The sensor according to any one of claims 11 to 14, wherein the well plate is a 6-well, 24-well, 96-well, or 384-well microwell plate.

Citation Information

Patent Citations

  • Microstructure and its production method

    JP2006083451A

  • Method and apparatus for detecting optical signal, sample cell for detecting optical signal, and kit for detecting optical signal

    JP2010190880A

  • Electric field enhancement element, analysis device, and electronic device

    JP2015114219A

  • Structured substrates for improved detection of optical radiation and methods related to structured substrates

    JP2017503483A

  • Hydrogel microarray with embedded metal nanoparticles

    US20080176768A1